Experimental study on the active repair and reinforcement of a shield tunnel lining with excessive transverse deformation - Junxian Xiao; Tingjin Liu; Haorui Ye; Yingpeng Jiang; Huifeng Wu; Huashan Zhong (Case Studies in Construction Materials)
The mechanical behavior of shield tunnel repairs under transverse ellipticity is critical for safety assessment and protection. However, the deformation behavior and reinforcement effectiveness of active repair techniques for tunnels with excessive deformation remain under investigation. This study introduces an innovative internal pressure-based active jacking system and examines the repair effects of various reinforcement strategies through 1:5 scale model experiments. On the basis of structural deformation characteristics, internal force distribution, failure modes, and toughness enhancements, the results indicate that a combination of local internal pressure and aramid fiber-reinforced polymer reinforcement (AFRP) active repair technology offers the greatest improvement in tunnel structure bearing capacity and stiffness, effectively inhibiting crack propagation. The reinforced structure exhibited a 36.4 % increase in stiffness and a 52.8 % improvement in toughness. Compared with traditional AFRP reinforcement, the active repair technique significantly delays the formation of plastic hinges, alters the internal force distribution, optimizes stress transfer pathways, and enhances tunnel stability and durability. The local internal pressure strengthened the bond between the AFRP and the concrete, creating a more robust composite bearing structure and significantly improving the energy absorption capacity of the structure. Furthermore, partial recovery of the tunnel’s ovality was found to be more effective than complete restoration, as it both increased the load capacity and reduced excessive warning thresholds, thereby ensuring structural safety and operational stability. These findings provide new insights for the repair and reinforcement of shield tunnels and hold significant engineering application value.